Extra-pulmonary manifestations of paracoccidioidomycosis associated with acquired immunodeficiency syndrome: a case report - Safe,Izabella Picinin (2014)
We present a patient with Paracoccidioidomycosis/HIV coinfection which has been investigated because of chronic monoarthritis and mucocutaneous lesions. A biopsy of the synovial membrane and skin revealed structures consistent with Paracoccidioides brasiliensis. At diagnosis, the count of CD4 + T cells was 44 cells/mm3. We emphasize the importance of clinical suspicion of Paracoccidioidomycosis in patients with HIV/AIDS who live in or are from risk areas.